Combining mapping of physiological quantitative trait loci and transcriptome for cold tolerance for counteracting male sterility induced by low temperatures during reproductive stage in rice. Issue 2 (18th March 2016) - Shimono, Hiroyuki; Abe, Akira; Aoki, Naohiro; Koumoto, Takemasa; Sato, Masahiro; Yokoi, Shuji; Kuroda, Eiki; Endo, Takashi; Saeki, Ken‐ich; Nagano, Kuniaki
Abstract : Male sterility induced by low temperatures (LTs) during the reproductive stage is a major constraint for temperate zone rice. To detect physiological quantitative trait loci (QTLs), we modeled genotypic variation in the physiological processes involved in low temperature spikelet sterility on the basis of anther length (AL), a proxy for microspore and pollen grain number per anther. The model accounted for 83% of the genotypic variation in potential AL at normal temperature and the ability to maintain AL at LT. We tested the model on 208 recombinant inbred lines of cold‐tolerant 'Tohoku‐PL3' (PL3) × cold‐sensitive 'Akihikari' (AH) for 2 years. QTLs for spikelet fertility (FRT) at LT were detected on chromosomes 5 ( Q TL for C old T olerance at R eproductive stage, qCTR5 ) and 12 ( qCTR12 ). qCTR12 was annotated with the ability to maintain AL under LTs. qCTR5 was in a region shared with QTLs for culm length and heading date. Genome‐wide expression analysis showed 798 genes differentially expressed in the spikelets between the parents at LTs. Of these, 12 were near qCTR5 and 23 were near qCTR12 . Gene expression analysis confirmed two candidate genes for qCTR5 ( O ‐methyltransferase ZRP4, Os05g0515600; beta‐1, 3‐glucanase‐like protein, Os05g0535100) and one for qCTR12 (conserved hypothetical protein, Os12g0550600). Nucleotide polymorphisms (21 deletions, 2 insertions and 10 single nucleotide polymorphisms) in PL3 were found near the candidate conserved hypothetical protein (Os12g0550600) and upstream in PL3, but not in AH. Haplotype analysis revealed that this gene came from 'Kuchum'. The combination of mapping physiological QTLs with gene expression analysis can be extended to identify other genes for abiotic stress response in cereals.